Optimization of Temperature and Drying Time of Encapsulated Synbiotic Powder on the Characteristics and Viability of Microcapsules - Lintang Dion Pangestu; I Made Dedi Mahariawan; Ating Yuniarti; Anik Martinah Hariati (Jurnal Penelitian Pendidikan IPA, 2025)
The drying process is often a problem in maintaining the stability of probiotics and the quality of microcapsules in the processing of synbiotic microencapsulation. This study aims to optimize the temperature and drying time to maintain the core material's stability and the microcapsules' quality. The research design in this study was a completely randomized design with two factorials, namely drying temperature (30°C, 35°C, and 40°C) and drying time (2, 2.5, and 3 hours). The results showed that the highest viability and efficiency values ​​were obtained in the drying process at 40°C for 2 hours, which were 9.29 log CFU/mL and 98.10%. In addition, the water content and gel strength of the microcapsules obtained also showed optimal conditions. Based on the results obtained, it can be concluded that the drying process at 40°C for 2 hours is the best treatment, with the highest viability and EE values ​​and low water content values.